Conservative surgical management of multiple myometrial abscesses; an unusual case with review of the literature - Gursoy, A. Yarci; Durdag, G. Dogan; Cetinkaya, E.; Cengiz, S. Dincer (I R O G Canada, Inc, 2015)
Myometrial abscess, especially with multiple foci, is quite rare and previous literature prevalently discusses unique locus of intramyometrial abscesses, usually treated with hysterectomy accompanied with or without bilateral salpingo-oophorectomy. The presented case, to the authors' knowledge, is the first multiple myometrial abscess case treated with conservative surgical approach.
Keywords: Intramyometrial; Abscess; Multiple; Conservative